Contribution of Leg Muscle Speed and Explosive Power to the Long Jump Ability of Students at SMPN 2 Galut - Zulfikar; Suparman; Suastika Nurafiati; Herman; Sarifuddin Arham (Indonesian Journal of Sport Management, 2025)
Background: The long jump results achieved by students at SMPN 2 Galut, Takalar Regency, are still low. This is due to the students' lack of understanding of the importance of speed and leg muscle explosive power. This study aims to determine the contribution of speed and explosive leg muscle power to long jump ability. This study uses a quantitative research method, specifically a correlational study with a population of 125 third-year students at SMPN 2 Galut in the even semester of 2023/2024. The research sample consisted of 30 people, selected using the simple random sampling technique. The research instruments for data collection were measurements of speed using a 40-meter running test, explosive leg muscle power using a standing long jump test, and measurements of long jump ability. Data analysis was performed using statistical calculations, namely correlation coefficients. The results of the data analysis showed that speed contributed to long jump ability with a coefficient of determination (R2) = 0.614 or 61.4%, and leg muscle power with a coefficient of determination (R2) = 0.390 or 39%. Long jump ability together contributed to long jump ability with a coefficient of determination (R2) = 0.624 or 62.4%. Therefore, to improve long jump ability, students need to increase speed and leg muscle explosive power training.